Occupation-related anxiety symptoms among teachers in Tshwane Metropolitan Municipality, South Africa - Kebogile Mokwena; Mathildah Mokgatle (Perspectives in Education)
Background: As the prevalence of mental disorders continues to increase, the workplace has been identified as one of the key sources of mental disorders. Over and above anxiety triggers that emerge from the teaching profession itself, societal and behavioural challenges among young people often extend to the school environment, which increases demands on teachers who have to manage such behaviours to make the classroom a place to operate. However, there are limited studies on the mental health status of teachers. Purpose of the study: The purpose was to screen for anxiety symptoms and identify risk factors among teachers in three school districts of Tshwane Municipality.